Community participation in the management of school facilities and infrastructure development - Nugraha Suharto; Edy Sofyan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
One of the accelerations to realize the process of building the nation and character is through the 9-Year Education Policy. This study aims to examine the differences in the influence of the characteristics of committee members on schools on the role of school committees in managing the development of school facilities and infrastructure in public junior high schools in Bandung regency. The approach used in this study is a quantitative approach with data processing techniques through the Multiple Classification Analysis (MCA) model. The results of this study revealed that the role of the School Committee in the Management of the Development of School Facilities and Elementary School Facilities was classified in the 'Good Enough' category. There is a significant difference in the influence of age, employment status, salary, and educational background on the role of the school committee in managing the development of school facilities and basic school facilities. Meanwhile, gender does not have a significant difference in influence, so the implication is that it is necessary to develop a model of empowerment in the community by paying attention to aspects of the recruitment of school committee members, the cooperation of school committee principals, and schools; and the demands and needs of the school.